The Efficiency of GFP Gene Transformation on Peanut Embryo somatic Using Agrobacterium and Particle Bombardment - Avivi, Sholeh; Dietzgen, Ralf G.; Higgins, Colleen M.; ., Sudarsono (UNEJ e-Proceeding, 2014)
The aims of this research were to (1) compare the effectiveness of established Agro bacterium mediated transformation and bombardment mediated transformation on peanut (2) evaluate the integration of green fluorescent protein (GFP) and hygromycin resistance (hygr) gene on the peanut embryosomatics. To achieve those objectives we shoot 1200 explants using bombardment and transform 1000 explants using Agrobacterium mediated transformation. Both of Agrobacterium mediated transformation and particle bombardment could give positive embryos transformed.Â  Particle bombardment gave 4.5% transformation efficiency while Agrobacterium mediated transformation gave only 1.8%. From this research, we concluded that particle bombardment more efficient and gave more transgenic explants than Agrobacterium mediated transformation. Keywords: agrobacterium, bombardment, GFP.